Avaliação da toxicidade dos sedimentos e da macrofauna bentônica em areas portuarias: porto do Mucuripe e terminal portuario do Pecem (CE) e porto de Santos (SP) - Moreira, Lucas Buruaem (2009)
Ports are important for the world economy; however, the activities related to them are considered very harmful the coastal systems, in special due to the contaminant inputs to the aquatic environment. Sediments constitute the main fate for the contaminants, and when contaminated, they may become a secondary source of contamination to the environment, threatening the health of ecosystems and affecting some economic activities, as fishing and dredging and disposal of dredged material. The objective of this study was to evaluate the quality of sediments from 3 port areas influenced by ports, by the ecotoxicological and ecological perspectives. Three Brazilian ports were selected: Ports of Mucuripe Pecém, both on the coast of Ceará State (Northeast of Brazil) and the Port of Santos, on the coast of São Paulo State (Southeast of Brazil). Sediments were characterized as to grain size distribution, content of carbonates, organic matter, total organic carbon, nitrogen and total phosphorus. The ecotoxicity assays employed the amphipod Tiburonella viscana (for wholes sediment) and embryos of the sea urchin Lytechinus variegates, for sedimentwater interface and the liquid phases extracted from the sediments (porewater and elutriates). The benthic community was evaluated for taxonomic composition and for some ecological descriptors, as total density (D - number of organisms), density of polychaetes, and the density of peracarida, richness (S) and Shannon-Weaner diversity (H’). Toxicity was found in sediments of the three areas, as to the amphipods as to L. variegatus larval development. The density, richness, abundance and diversity indices were considered low, indicating that the benthic communities are under stress. The integrative analysis indicated that as the natural factors, such as hydrodynamic, different water masses, and sediment composition, as the toxicity of the sediments, which is the ultimate integrated expression of the contamination, influenced on the benthic fauna composition. The results showed that the applied methods may be used as a tool to subsidize the sediment quality assessment and the management of dredged materials.